Alienasi Perempuan pada Novel Pasola Karya Maria Matildis Banda (Pendekatan Psikologi Sastra) - Natalia Santiari Henuk; Marselus Robot; Karolus Budiman Jama (Lembaga Yasin AlSys, 2026)
The novel Pasola by Maria Matildis Banda represents the lives of women who experience various forms of alienation due to patriarchal culture, social norms, and traditions that restrict their freedom. This study aims to describe the forms, causal factors, and impacts of alienation experienced by the female characters in the novel. The study employed a qualitative approach using a descriptive method and a literary psychology perspective based on Erich Fromm’s theory of alienation. The data source was the novel Pasola, while the data consisted of textual passages representing female alienation. The data were collected through documentation and coding techniques and were then analyzed through the stages of identification, classification, and interpretation. The results revealed 31 instances encompassing two forms of alienation, four causal factors, and four impacts of alienation. The forms of alienation consisted of alienation from oneself (self-alienation) and social alienation. The factors causing alienation included transcendence, rootedness, relatedness, and frame of orientation and devotion. The impacts of alienation included self-alienation, stress, anxiety and depression, superficial social relationships, and the loss of autonomy and creativity. These findings indicate that the female characters in the novel experience alienation due to the dominance of social systems and patriarchal culture that restrict their freedom, identity formation, and social relationships. This study contributes to the development of literary psychology studies, particularly the application of Erich Fromm’s theory of alienation, and enriches the understanding of the representation of women’s psychological experiences in Indonesian literary works.